2015
DOI: 10.1021/acs.jpclett.5b00324
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs in Capacity and Rechargeability in Nonaqueous Li–O2 Batteries: Solution-Driven Growth versus Nucleophilic Stability

Abstract: The development of high-capacity rechargeable Li-O2 batteries requires the identification of stable solvents that can promote a solution-based discharge mechanism, which has been shown to result in higher discharge capacities. Solution-driven discharge product growth requires dissolution of the adsorbed intermediate LiO2*, thus generating solvated Li+ and O2(-) ions. Such a mechanism is possible in solvents with high Gutmann donor or acceptor numbers. However, O2(-) is a strong nucleophile and is known to atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
158
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(167 citation statements)
references
References 36 publications
5
158
0
4
Order By: Relevance
“…However, there is tremendous scope in tuning the electrolyte anion in low-DN solvents to obtain high discharge capacities. Given that it should be simpler to identify anions stable to the Li-O 2 cathode electrochemistry than high-DN solvents (36,37), anion selection in combination with low-DN solvents potentially provides a route to avoid the unfavorable capacity/stability trade-off observed in high-DN solvents, such as DMSO (14,15,38,39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is tremendous scope in tuning the electrolyte anion in low-DN solvents to obtain high discharge capacities. Given that it should be simpler to identify anions stable to the Li-O 2 cathode electrochemistry than high-DN solvents (36,37), anion selection in combination with low-DN solvents potentially provides a route to avoid the unfavorable capacity/stability trade-off observed in high-DN solvents, such as DMSO (14,15,38,39).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, using quantitative measures of battery rechargeability, high-DN solvents, such as DMSO and N-methyl pyrrolidone, have been observed to be less stable than low-DN solvents, such as acetonitrile and DME (14). Recently, Khetan et al used a thermodynamic analysis to show that an organic solvent's ability to induce the solution mechanism is anticorrelated with its stability toward nucleophilic attack (15 (16,17). We found that electrolytes containing a high concentration of NO 3 − exhibited higher donicity, as verified using 7 Li NMR, and provided an increase in battery capacity greater than fourfold compared with a battery using exclusively TFSI − as the electrolyte anion, while not decreasing battery rechargeability, as measured using quantitative oxygen consumption and evolution.…”
Section: Significancementioning
confidence: 99%
“…[50] As Li + solvation structures can vary greatly among similar solvents (for example, glymes), [51,52] and across different classes of solvents such as ionic liquids, [53] À potentials. These results highlight the importance of the interplay between ion-solvent and ion-ion interactions in understanding and controlling the intermediate species energetics, reaction product morphology, discharge capacity, and solvent stability in aprotic metal-O 2 batteries.…”
mentioning
confidence: 99%
“…27 Ideally, future electrolyte solvents should possess high AN or DN to facilitate toroid formation and maximize discharge capacity without exacerbating by-product formation. 28,29 The search for more stable electrolyte and cathode pairings for Li-O 2 batteries has become a critical area of research and will likely determine the long term prospects of the Li-O 2 system. 30,31 To date, the pursuit of sufficiently stable electrolytes (i.e.…”
mentioning
confidence: 99%